(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Context: There is need to develop cheap and effective natural excipient that can be used as an alternative in pharmaceutical formulation due to their non-toxicity, easy availability, biodegradability, and biocompatibility. Aims: The purpose of this research was to develop and evaluate sustained release matrix tablets of metoprolol tartrate based on natural gum exudates of Butea monosperma. Materials and Methods: B. monosperma gum was characterized for its properties such as compressibility index, angle of repose, viscosity, and moisture content. The interaction between the gum and metoprolol tartrate was studied through differential scanning calorimetry and Fourier transform infrared spectroscopy. Matrix tablets were prepared by wet granulation method with different concentrations of B. monosperma gum and guar gum and evaluated for their physical properties such as weight variation, hardness, friability, and content uniformity. A dissolution study was conducted to characterize the release mechanism from the matrix system, and data were fitted to various kinetic models. Results: The mechanism of drug release from both types of matrix tablets was found to be anomalous type. The F5 batch prepared using B. monosperma gum shows 92.45% release in 24 h. Conclusions: B. monosperma gum could be used as drug release retardant in sustained release matrix systems.